2018
DOI: 10.1111/vsu.12792
|View full text |Cite
|
Sign up to set email alerts
|

Once daily oral extended‐release hydrocodone as analgesia following tibial plateau leveling osteotomy in dogs

Abstract: Our results do not provide evidence to justify the administration of extended-release hydrocodone at 3 mg/kg orally every 24 hours rather than firocoxib at 5 mg/kg orally every 24 hours in dogs undergoing tibial plateau leveling osteotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Other force plate studies in dogs using a similar urate crystal model of induced synovitis showed that firocoxib produced substantial improvements in lameness, and three studies found that lameness in firocoxib treated groups was significantly less than in carprofen or robenacoxib treated dogs [5, 7, 10]. Force plate assessments of analgesia following tibial plateau levelling osteotomy found that firocoxib provided analgesia that was superior to robenacoxib, tramadol, and hydrocodone in three separate studies [15, 16]. The findings of force plate studies align with three field studies in which dog owner evaluations found significant improvements for firocoxib over etodolac, carprofen and deracoxib [2, 17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Other force plate studies in dogs using a similar urate crystal model of induced synovitis showed that firocoxib produced substantial improvements in lameness, and three studies found that lameness in firocoxib treated groups was significantly less than in carprofen or robenacoxib treated dogs [5, 7, 10]. Force plate assessments of analgesia following tibial plateau levelling osteotomy found that firocoxib provided analgesia that was superior to robenacoxib, tramadol, and hydrocodone in three separate studies [15, 16]. The findings of force plate studies align with three field studies in which dog owner evaluations found significant improvements for firocoxib over etodolac, carprofen and deracoxib [2, 17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Reported complications associated with ESWT include mild bruising, redness, transient superficial pain at the treatment site, and the requirement for sedation or general anesthesia for treatment . Subjective pain evaluation 24 hours after surgery in this study may not have been of sufficient resolution to detect differences between treatments, although the rubric used is well established for comparison of postoperative comfort levels . More objective forms of pain evaluation, such as kinetic gait, mechanical threshold testing with an algometer, or stance analysis, could have been performed …”
Section: Discussionmentioning
confidence: 99%
“…15,39,40 Subjective pain evaluation 24 hours after surgery in this study may not have been of sufficient resolution to detect differences between treatments, although the rubric used is well established for comparison of postoperative comfort levels. 4,41,42 More objective forms of pain evaluation, such as kinetic gait, mechanical threshold testing with an algometer, or stance analysis, could have been performed. 43,44 Additional stifle measures including circumference to quantitate joint effusion 27 and periarticular swelling and joint angles to quantitate range of motion also did not show much difference among treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Of the drugs utilized by survey participants, tramadol was the most commonly prescribed for outpatient use (245 out of 458, 53.5%) followed by buprenorphine (126 out of 475, 26.5%) and hydrocodone (98 out of 342, 28.7%). Although not specifically explored in the survey, it is likely that hydrocodone is prescribed primarily for cough suppression rather than pain control (20). Buprenorphine is often a good choice for postoperative pain control in dogs and cats and has the advantages of long lasting analgesic effect (~8 h) and high bioavailability following trans-mucosal administration (2124).…”
Section: Discussionmentioning
confidence: 99%